The Influence Of Transformation Al Leadership On Organizational Citizenship Behavior With Interpersonal Trust As A Mediation Variable At PT. Digital Mediia Telematics) - Ratna Dwi Jayanti (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This research aims to analyze and explain how transformational leadership influences Organizational Citizenship Behavior (OCB) behavior with interpersonal trust as an intermediary variable in PT. Digital Media Telematics Perak Branch. This research uses a quantitative approach and explanatory research methods. The research sample consisted of 33 employees of PT. Digital Media Telematics Perak Branch. The analysis techniques used include validity tests, reliability tests, descriptive analysis and SEM analysis with the help of SmartPLS 4.0 software. Research findings show that transformational leadership can improve Organizational Citizenship Behavior (OCB) behavior, as well as interpersonal trust. Apart from that, interpersonal trust also acts as a mediator that influences the relationship between transformational leadership and Organizational Citizenship Behavior (OCB).